Professor Nikolaos Louros, a concerned scientist in twentieth-century Athens - Gardikas, Katerina (DELTOS, 2024)
The personal papers of Nikolaos Louros present an invaluable source of information on Louros’s place in the medical, social, cultural and political history of twentieth-century Greece. A royalist, liberal and keen observer of scientific and social developments, he participated actively in the shaping of the country’s post-war progress in medical education, institutions and ideas.